Nasogastric Tube Feeding Practice and Associated Complication in stroke Patients in a Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Nasogastric tube feeding is an integral part of management of stroke patients with feeding difficulties.Objectives: The purpose of the present study was to evaluate the nasogastric tube feeding practice and its complication on stroke patients.Methodology: One hundred (100) adult patients aged ≥ 18 years with stroke were enrolled in the study. The diagnosis of stroke was established by the clinical presentation, neuroimaging. Patients requiring nasogastric tube feeding was included in the study. They were thoroughly examined for any complications from possible use of nasogastric tube. Their caregivers were also thoroughly interviewed using a standard preformed questionnaire regarding any complications as well. Results: A total number of 100 patients were recruited for this study. In this study population, 63.0% patients had ischaemic stroke; 26.0% had haemorrhagic stroke and 9.0% population had sub-arachnoid haemorrhage. The most common indication for NG feeding was difficulty in swallowing (39.0%) followed by semi consciousness (26.0%), unconsciousness (22.0%), inability to maintain feed (10.0%). About 71.0% of the patients had complications from NG tube feeding such as nasal irritation (53.0%), electrolyte imbalance (43.0%), aspiration pneumonia (40.0%) and diarrhea (38.0%).Conclusion: Nasal irritation, aspiration pneumonia, electrolyte imbalance, diarrhea are common complications associated with NG tube feeding which in part may be related to faulty feeding technique.Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 23-27